β1 integrins regulate mammary gland proliferation and maintain the integrity of mammary alveoli - Li, Na (Nature Publishing Group, 2005)
Integrin–extracellular matrix interactions play important roles in the coordinated integration of external and internal cues that are essential for proper development. To study the role of β1 integrin in the mammary gland, Itgβ1(flox/flox) mice were crossed with WAPiCre transgenic mice, which led to specific ablation of β1 integrin in luminal alveolar epithelial cells. In the β1 integrin mutant mammary gland, individual alveoli were disorganized resulting from alterations in cell–basement membrane associations. Activity of focal adhesion kinase (FAK) was also decreased in mutant mammary glands. Luminal cell proliferation was strongly inhibited in β1 integrin mutant glands, which correlated with a specific increase of p21(Cip1) expression. In a p21(Cip1) null background, there was a partial rescue of BrdU incorporation, providing in vivo evidence linking p21(Cip1) to the proliferative defect observed in β1 integrin mutant glands. A connection between p21(Cip1) and β1 integrin as well as FAK was also established in primary mammary cells. These results point to the essential role of β1 integrin signaling in mammary epithelial cell proliferation.